Three- Versus Two-Drug Therapy for Patients With Newly Diagnosed Pulmonary Arterial Hypertension - Chin, Kelly M.; Sitbon, Olivier; Doelberg, Martin; Feldman, Jeremy; Gibbs, J. Simon R.; Grünig, Ekkehard; Hoeper, Marius M.; Martin, Nicolas; Mathai, Stephen C.; McLaughlin, Vallerie V.; Perchenet, Loïc; Poch, David; et al. (Journal of the American College of Cardiology, 2021)
In pulmonary arterial hypertension (PAH), there are no data comparing initial triple oral therapy with initial double oral therapy. TRITON (The Efficacy and Safety of Initial Triple Versus Initial Dual Oral Combination Therapy in Patients With Newly Diagnosed Pulmonary Arterial Hypertension; NCT02558231), a multicenter, double-blind, randomized phase 3b study, evaluated initial triple (macitentan, tadalafil, and selexipag) versus initial double (macitentan, tadalafil, and placebo) oral therapy in newly diagnosed, treatment-naive patients with PAH. Efficacy was assessed until the last patient randomized completed week 26 (end of main observation period). The primary endpoint was change in pulmonary vascular resistance (PVR) at week 26. Patients were assigned to initial triple (n = 123) or initial double therapy (n = 124). At week 26, both treatment strategies reduced PVR compared with baseline (by 54% and 52%), with no significant difference between groups (ratio of geometric means: 0.96; 95% confidence interval: 0.86-1.07; P = 0.42). Six-minute walk distance and N-terminal pro–brain natriuretic peptide improved by week 26, with no difference between groups. Risk for disease progression (to end of main observation period) was reduced with initial triple versus initial double therapy (hazard ratio: 0.59; 95% confidence interval: 0.32-1.09). Most common adverse events with initial triple therapy included headache, diarrhea, and nausea. By the end of the main observation period, 2 patients in the initial triple and 9 in the initial double therapy groups had died. In patients with newly diagnosed PAH, both treatment strategies markedly reduced PVR by week 26, with no significant difference between groups (primary endpoint not met). Exploratory analyses suggested a possible signal for improved long-term outcomes with initial triple versus initial double oral therapy. [Display omitted]